An Electrochemical Biosensor Analysis of the Interaction of a Two-Vector Phospholipid Composition of Doxorubicin with dsDNA and Breast Cancer Cell Models In Vitro - Lyubov V. Kostryukova; Anastasia S. Serdyukova; Veronica V. Pronina; Victoria V. Shumyantseva; Yulia A. Tereshkina (Pharmaceutics)
Objectives: The main aim of our experiments was to demonstrate the suitability of cell-based biosensors for searching for new anticancer medicinal preparations. Methods: The effect of the substance doxorubicin, doxorubicin embedded in phospholipid nanoparticles, and doxorubicin with phospholipid nanoparticles modified by targeting vectors (cRGD and folic acid) on dsDNA and breast cancer cell lines (MCF-7, MDA-MB-231) was studied. Results: In the obtained doxorubicin nanoforms, the particle size was less than 60 nm. Our study of the percentage of doxorubicin inclusion showed the almost complete embeddability of the substance into nanoparticles for all samples, with an average of 95.4 ± 4.6%. The calculation of the toxicity index of the studied doxorubicin samples showed that all substances were moderately toxic drugs in terms of adenine and guanine. The biosensor analysis using electrodes modified with carbon nanotubes showed an intercalation interaction between doxorubicin and its derivatives and dsDNA, except for the composition of doxorubicin with folic acid with a linker length of 2000 (NPh-Dox-Fol(2.0)). The results of the electroanalysis were normalized to the total cell protein (mg) and cell concentration. The highest intensity of the electrochemical signals was observed in intact control cells of the MCF-7 and MDA-MB-231 cell lines. Conclusions: The proposed electrochemical approach is useful for the analysis of cell line responses to the medicinal preparations.